Pengaruh Media Virtual Reality terhadap Motivasi Belajar PAI pada Materi Sejarah Peradaban Islam Siswa Kelas XI DKV di SMK Informatika Sumedang - Kushendriyana, Febrian; Hamid, Eka Abdul; Zaelani, Moh. Ichsan (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
This study was motivated by the decline in student motivation to learn Islamic Civilization History. This phenomenon, which affects student motivation, arises because conventional teaching methods are not interactive enough, making it difficult for students to visualize and clearly relate historical events. In addition, intense distractions from viral media also erode their enthusiasm and motivation to learn, causing difficulties in understanding the concepts of Islamic civilization history and impacting students' motivation to learn. Virtual Reality (VR) media has been identified as an innovative solution with the potential to create an interactive and immersive learning experience. The purpose of this study was to examine the effect of VR media on increasing PAI learning motivation in Islamic Civilization History material among 11th grade DKV students at SMK Informatika Sumedang. This quantitative research with a survey approach involved 29 respondents from the 11th grade DKV class at SMK Informatika Sumedang using the saturated sampling technique, in which the entire population was used as the sample. Data were collected through questionnaires and analyzed statistically using t-tests, simple linear regression, and correlation coefficients. The results showed that VR had a positive and significant effect on learning motivation. Statistically, the t-count was 3.912 > t-table 2.052, with a significance of 0.001 (p < 0.05). The positive regression coefficient (0.310) and correlation coefficient (r) of 0.759 indicate a very strong relationship. The contribution of VR to learning motivation reached 36%. Descriptive analysis also shows that VR increases student engagement, visualization understanding, and motivation. In conclusion, Virtual Reality Media has been proven effective in increasing learning motivation. It is recommended that SMK Informatika Sumedang implement and optimize the continuous use of VR, supported by teacher readiness and infrastructure.